Imaging of Chlorophyll a Fluorescence in Natural Compound-Induced Stress Detection - Sánchez-Moreiras, Adela M.; Graña, Elisa; Reigosa, Manuel J.; Araniti, Fabrizio (Frontiers in Plant Science, 2020)
Imaging of chlorophyll a fluorescence (CFI) represents an easy, precise, fast and non-invasive technique that can be successfully used for discriminating plant response to phytotoxic stress with reproducible results and without damaging the plants. The spatio-temporal analyses of the fluorescence images can give information about damage evolution, secondary effects and plant defense response. In the last years, some studies about plant natural compounds-induced phytotoxicity have introduced imaging techniques to measure fluorescence, although the analysis of the image as a whole is often missed. Therefore, we present in this study the advantages of monitoring fluorescence images, presenting the physiological interpretation of different possible combinations of the most relevant parameters linked to fluorescence emission and the images obtained, to highlight the advantages of this imaging technique through comparison of their effects on plant metabolism.